Hubungan Umur, Paritas dan Anemia dengan Kejadian Perdarahan Post Partum di Charitas Hospital Palembang Tahun 2021 - Lucia Sugiyarni; Rizki Amalia; Andini Zuitasari; Ahmad Arif (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Post-partum haemorrhage is defined as the loss of more than 500 ml or more blood after giving birth. Maternal Mortality Rate (MMR) in South Sumatera Province based on Health Profile in the year of 2018 reported that 46 people died because of haemorrhage, 29 died because of hypertension, 2 people died because of metabolic disorder. Meanwhile, there were 28 people from another city reported died. In 2019, the number of MMR in South Sumatera Province showed that there were 128 deaths out of 158.251 live births. This study was aimed to find out the correlation between age, parity and anaemia with the incidence of post partum haemorrhage in Charitas Hospital Palembang year 2021. This study applied cross sectional method. The population of this study was taken from all maternity mothers at Charitas Hospital Palembang. There were 555 respondents. The samples were 85 mothers who were taken by applying random sampling method. The data analysed were the secondary data taken from medical record. The data analysed were the seclolndary data taken from medical record. The result of this study showed that the incidence of post partum haemorrhage in Charitas Hospital Palembang in 2021. Statistic test showed that p = 0.002 or p ≤ 0.05. There was a significant correlation between parity and the incidence of post-partum haemorrhage in Charitas Hospital Palembang in 2021. Statistic test showed that p = 0.009 or p ≤ 0.05. there was a significant correlation between anaemia and the incidence of post partum haemorrhage in Charitas Hospital Palembang in 2021. Statistic test showed that p = 0.001 or p ≤ 0.05. It is essential that health workers monitor maternity mothers health to provent anaemia and give qualified maternity care to prevent post partum haemorrhage.